2005
DOI: 10.1093/hmg/ddi180
|View full text |Cite
|
Sign up to set email alerts
|

A novel functional VKORC1 promoter polymorphism is associated with inter-individual and inter-ethnic differences in warfarin sensitivity

Abstract: Warfarin, a commonly prescribed anticoagulant, exhibited large inter-individual and inter-ethnic differences in the dose required for its anticoagulation effect. Asian populations, including Chinese, require a much lower maintenance dose than Caucasians, for which the mechanisms still remain unknown. We determined DNA sequence variants in CYP2C9 and VKORC1 in 16 Chinese patients having warfarin sensitivity (< or = 1.5 mg/day, n = 11) or resistance (> or = 6.0 mg/day, n = 5), 104 randomly selected Chinese patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
293
2
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(339 citation statements)
references
References 29 publications
35
293
2
9
Order By: Relevance
“…1). Recently, several groups have demonstrated that polymorphisms in VKORC1 are associated with warfarin sensitivity (D'Andrea et al 2005;Wadelius et al 2005;Yuan et al 2005;Rieder et al 2005;Sconce et al 2005). In a Swedish study, weekly warfarin doses varied significantly, and were associated with four VKORC1 SNPs (5¢ flankingÀ1413A>G, intron 1À136T>C, intron 2+837T>C and exon 3 343G>A), similar to our results (Wadelius et al 2005).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…1). Recently, several groups have demonstrated that polymorphisms in VKORC1 are associated with warfarin sensitivity (D'Andrea et al 2005;Wadelius et al 2005;Yuan et al 2005;Rieder et al 2005;Sconce et al 2005). In a Swedish study, weekly warfarin doses varied significantly, and were associated with four VKORC1 SNPs (5¢ flankingÀ1413A>G, intron 1À136T>C, intron 2+837T>C and exon 3 343G>A), similar to our results (Wadelius et al 2005).…”
Section: Discussionsupporting
confidence: 89%
“…In a Swedish study, weekly warfarin doses varied significantly, and were associated with four VKORC1 SNPs (5¢ flankingÀ1413A>G, intron 1À136T>C, intron 2+837T>C and exon 3 343G>A), similar to our results (Wadelius et al 2005). Yuan et al (2005) demonstrated that Chinese patients homozygous for the major allele of the À1413A>G polymorphism required a lower warfarin dose than those with other genotypes. The authors also suggested that the promoter polymorphism abolished the E-box consensus sequences, leading to a 44% increase in promoter activity for the minor allele compared to the major allele.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A prospective study addressing the question of whether a priori knowledge of CYP2C9 genotype may improve warfarin therapy demonstrated that patients who were treated applying a CYP2C9 genotype-adjusted algorithm reached a significantly earlier stable anticoagulation state and experienced less minor bleeding [3] than those who were not. Moreover, subjects who are carriers of variants in the vitamin K epoxide reductase complex, subunit 1 (VKORC1) gene require significantly higher warfarin doses than usually recommended [5,30]. In order to estimate appropriate warfarin dosing, algorithms based on both clinical and genetic data obtained from a broad population base have been calculated in a large cohort, thereby achieving a better prediction of subjects requiring lower doses of warfarin for therapeutic anticoagulation [15].…”
Section: Application Of Personal Medicine In Clinical Practicementioning
confidence: 99%